The control of drilling vibrations: A coupled PDE-ODE modeling approach - Saldivar, Belem; Mondié, Sabine; Ávila Vilchis, Juan Carlos (Zielona Góra: Uniwersytet Zielonogórski)
The main purpose of this contribution is the control of both torsional and axial vibrations occurring along a rotary oilwell drilling system. The model considered consists of a wave equation coupled to an ordinary differential equation (ODE) through a nonlinear function describing the rock-bit interaction.
Keywords: drilling vibrations; LMI approach; ultimate boundedness; coupled wave-ODE system